Usability Elements in Digital Textbook Development: A Systematic Review - Wan Sulaiman, Wan Noor Azhar; Mustafa, Siti Ezaleila (Springer Verlag, 2020)
The growth of digital technology triggers a new wave to the development of new media alternative including digital textbook. A variety of digital textbook formats and the content is easily transportable cross media can lead to complexity of user expectations. Considering usability elements is one of the critical successful factors to ensure the digital textbook meets the user expectation. Despite, overwhelming research and standards pertaining usability, there is still a lack of efforts to systematically review the concept of usability elements in the digital textbook development context. The research seeks at addressing this gap by evaluating the current literature on the notion of usability components regarded in digital textbook development. A systematic analysis of the Scopus and Web of Science databases acknowledged 17 related studies from 213 journal articles, guided by the evaluation method of the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). Further review of these articles resulted 17 usability factors have been identified. These usability factors further produced a total of 49 usability properties. The review provides a better understanding of usability factors and criteria that need to be considered in the development of digital textbook and shows that usability elements is crucial for improving the digital textbook quality. In addition, this research provides a basis for the future research in usability elements of digital textbook. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.